2012
DOI: 10.1158/1940-6207.capr-11-0551
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Activates p38/JNK and Inhibits Erk1/2 Leading to Caspase-Independent Cell Death in Tumor Cells

Abstract: Cryptotanshinone (CPT), a natural compound isolated from the plant Salvia miltiorrhiza Bunge, is a potential anticancer agent. However, the underlying mechanism is not well understood. Here, we show that CPT induced caspase-independent cell death in human tumor cells (Rh30, DU145, and MCF-7). Besides downregulating antiapoptotic protein expression of survivin and Mcl-1, CPT increased phosphorylation of p38 mitogen-activated protein kinase (MAPK) and c-jun N-terminal kinase (JNK), and inhibited phosphorylation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…28 It has been found that CPT leads to caspaseindependent cell death in Rh30 and DU145 cells by activating p38/JNK signaling and inhibiting Erk1/2 signaling in a reactive oxygen species (ROS) dependent manner. 22 CPT has been found to induce MCF7 cell apoptosis in a similar manner. Additionally, recent studies demonstrated that CPT induces endoplasmic reticulum (ER) stress-mediated apoptosis in MCF7 cell via ROS generation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…28 It has been found that CPT leads to caspaseindependent cell death in Rh30 and DU145 cells by activating p38/JNK signaling and inhibiting Erk1/2 signaling in a reactive oxygen species (ROS) dependent manner. 22 CPT has been found to induce MCF7 cell apoptosis in a similar manner. Additionally, recent studies demonstrated that CPT induces endoplasmic reticulum (ER) stress-mediated apoptosis in MCF7 cell via ROS generation.…”
Section: Discussionmentioning
confidence: 80%
“…[14][15][16][17] Recently, CPT has also been reported to have obvious antitumor activity in a variety of cancer cells, including prostate carcinoma, hepatocarcinoma, rhabdomyosarcoma and melanoma cells. [18][19][20][21][22][23] In breast carcinoma cells, CPT has been shown to inhibit MCF7 cell proliferation by suppressing mTOR mediated CyclinD1 expression and Rb phosphorylation that lead to MCF7 cell apoptosis by inducing stress in the endoplasmic reticulum (ER). 24,25 However, it is not known whether CPT has any effects on estrogen-stimulated ER signaling and estrogen /ER mediated cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…CPT has been previously shown to inhibit growth and induce apoptosis in a number of human cancer cell lines [11]. In prostate cancer cells, CPT induced cell apoptosis by suppressing mammalian target of rapamycin (mTOR)-mediated cyclin D1 expression [12] and inhibiting Stat3 activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, data have shown that CPT is the most potent anticancer agent among the extracts of Danshen, by inhibiting proliferation of cancer cells or inducing cell apoptosis (Chen et al, 2010;Chen et al, 2012), but its function on MCF-7 cells still rarely reported. The (Nizamutdinova et al, 2008), therefore, it is important to identify new agents that is effective in breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Considered that breast cancer is the most prevailing disease among all cancers (Soerjomataram et al, 2012), and previous reports have showed that CPT induces ROS release which activates p38/JNK and inhibits Erk1/2, leading to caspase-independent cell death of human tumor cells (Rh30, DU145, and MCF-7) (Chen et al, 2012), we wondered is that possible CPT inhibits MCF7 cells grow in vivo? If so, how does it perform its antitumor function?…”
Section: Introductionmentioning
confidence: 99%